MEDICATION AND APPROPRIATE PHYSICAL THERAPY OF COMPLEX REGIONAL PAIN SYNDROME PATIENTS AFTER TRAUMA - Elizabeta, P. R.; Anastasika, P.; Leonid,; R. (BALI MEDICAL JOURNAL, 2013)
Objective: Treatment of patients with complex regional pain syndrome (CRPS) after trauma needs a complex physical and medical therapy, according of the stage of condition. The patient with trauma is coming to rehabilitation department, after surgery treatment. The aim of our study is to represent the effect of complexity physical therapy and medical support in treatment of patients with CRPS with evaluation of decrease of pain and increase of function in affected region. Method: we are treating 35 patients overage 35-70 years with 2 including criteria, clinical reaction of CRPS and radiological changes of osteoporosis. Medication includes non steroidal anti-inflammatory drugs, tricycle anti-depressants, vasoactive drugs and calcitonin. Physical therapy is consisting of electro therapy, sonophoresis and paraffin. Results: The evaluation was made with observation and measurement of pain, swelling and color of skin and movements of the joint. Conclusion: the goodness of the condition with whole time of rehabilitation 3-6 months was significant p < 0.01.